LEGAL ISSUES RELATED TO THE FLIGHT OF PEASANTS IN OLD POLAND (14th-19th CENTURY) - Konarski, Marcin Jerzy (Review of European and Comparative Law, 2019)
In the light of old Polish law, based on the system of norms of peasant slavery, understood as a legal institution, the flight of peasants was qualified as an illegal act, which was subject various legal sanctions. The reason why peasants chose to become fugitives was usually their desire to improve living conditions. The direction the fugitives took was another village (a different demesne), a town (private or royal); peasants even crossed state borders. This analysis draws attention to the most important legal problems related to the flight of peasants in former Poland concerning the sources of law as regards the flight of peasants, ways of seeking to release a peasant by means of court proceedings, types of sanctions for such flight, and forms of peasants' abandonment of master's property other than flight.